A double-blind, placebo-controlled, randomized, multi-centre, phase III study of MLC901 (NeuroAiDTMII) for the treatment of cognitive impairment after mild traumatic brain injury. - Pavel I Pilipenko; Anna A Ivanova; Yulia V Kotsiubinskaya; Vera N Grigoryeva; Alexey Y Khrulev; Anatoly V Skorokhodov; Maxim M Gavrik; Nona N Mkrtchan; Marek Majdan; Peter Valkovic; Daria Rabarova; Suzanne Barker-Collo; et al. (PLoS ONE)
Introduction About half of the world population will suffer from a traumatic brain injury (TBI) during their lifetime, of which about 90% of cases are mild TBI. Although up to 40% of adults with mild TBI experience persistent functional deficits, there is no proven-effective treatment to facilitate recovery after it. Methods and analysis This randomized placebo-controlled multi-centre study was aimed to examine the efficacy of herbal supplement MLC901 on complex attention following mild TBI at 6 months post-randomisation, as a primary outcome measured by CNS Vital signs (CNS-VS). Adults aged 18-65 years, who were 1-12-months post-mild TBI and experienced cognitive impairment, were randomly assigned to receive either MLC901 two capsules (0.4g/capsule) or placebo three times a day for 6 months using centralized stratified permuted block randomization. Secondary outcomes: Rivermead Post-Concussion Symptoms Questionnaire (RPQ; neurobehavioral sequelae); Health Related Quality of Life (QOLIBRI); Hospital Anxiety and Depression Scale (HADS); and safety. Mixed effects models of repeated measures with intention to treat analysis were employed. A Least Square Mean Difference (LSMD) from baseline to 3-, 6-, and 9-month follow-up was calculated with 95% confidence intervals (CI). Results In the analysis, 182 participants (47.8% females) were included. Multivariable mixed effects model analysis did not reveal significant improvements in complex attention (LSMD = -1.18 [95% CI -5.40; 3.03; p = 0.58]) and other cognitive domains at 6 months in the MLC901 group compared to the Placebo group. There were significant improvements in RPQ, QOLIBRI, anxiety and depression in the MLC901 group compared to the Placebo group at 6 and 9 months (LSMD -4.36 [-6.46; -2.26] and -4.07 [-6.22; -1.92], 4.84 [1.58; 8.10] and 3.74 [0.44; 7.03], -1.50 [-2.29; -0.71 and -0.96 [-1.84; -0.08], -1.14 [-1.92; -0.35] and -1.14 [-1.94; -0.34]), respectively. MLC901 tested was proven safe. Conclusions Although the 6-month treatment with MLC901 did not result in a statistically significant difference with placebo for CNS-VS measurement of cognitive domains in individuals with mild TBI, the study showed a clinically and statistically significant improvement in all clinical scales assessed by the investigators. Trial registration ClinicalTrials.gov identifier NCT04861688.